Building subnational capacities in animal health to deliver frontline cross-sectoral health services in Kenya - Sitawa, Rinah; Tenge, Evans; Chepkorir, Khadija; Nanyingi, Mark; Okuthe, Sam; Lockhart, Caryl; Oyas, Harry; Njagi, Obadiah; Agutu, Mary Teresa; Omolo, Jack; Okumu, Tequiero; Bebay, Charles; et al. (Frontiers in Veterinary Science, 2023)
Operationalizing effective subnational veterinary services as major contributor to disease surveillance, reporting, diagnoses and One Health requires resources and mindset change. Here we describe workforce capacity building in animal health in Kenya and an approach that can be used to skill-up this workforce to respond beyond animal health challenges to emergent One Health realities and public health emergencies.Furthermore, triggering a paradigm shift has been identified for impactful delivery of health services, thus mindset change are important for learning new skills, but they also affect the way that we think about everything, for instance training in field epidemiology. Emphasis was therefore placed on skills, beliefs, and mindset shift. Contextualized within the Kenyan environment, this description identifies problems likely to be found elsewhere: They are a). The limited Programs that offer structured and routine on-thejob training for animal health workers; b). Unequal distribution and inadequate quantity and quality of highly skilled workforce with appropriate technical training and scientific skills to combat public (and animal) health challenges at the frontline; c). Health challenges occasioned by climate change and drought, feed, and water scarcity; and d). Inadequate contingency, preparedness, and response planning for effective deployment of ready-to-trigger workforce capacity. In-Service Applied Veterinary Epidemiology Training (ISAVET) is a four-month long training program targeted at capacity building of frontline animal health professionals. The training, which is currently implemented in 17 African countries, is innovative and a customized field epidemiology program, which responds to specific needs in animal health and contribute to approaches utilizing One Health.A four-month long training was implemented, and several trainees had a marked mindset change as shown in the outputs and outcomes. Positive attitudes towards improving animal health surveillance were noted during the evaluation process. Most existing workforce capacities in the animal and public health systems were built for specific fields, and hardly respond optimally for cross-sectoral purposes. We proposed customised in-service applied veterinary epidemiology training that bypasses narrow-scoped workforce development but meets multifunctional, multidisciplinary and multisectoral needs before and during emergencies.